2021
DOI: 10.3390/polysaccharides2040047
|View full text |Cite
|
Sign up to set email alerts
|

Chitin as a Sorbent Superior to Other Biopolymers: Features and Applications in Environmental Research, Energy Conversion, and Understanding Evolution of Animals

Abstract: Chitin is an effective sorbent which can be used in environmental monitoring, beyond obvious applications in withholding metal-containing pollutants from wastewater- or nuclear fuel reprocessing flows, since background levels in (purified) chitin are very low except for a few metals (Fe, Cu, Al, Ti, and Zn). Since retention of Mx+ and their complexes on chitin depend on an oxidation state, and to a lesser extent the presence of possible ligands or co-ligands, partition between chitin samples exposed to sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Based on previous research by the working group, it has been found that metals can be desorbed from chitin (Sigma-Aldrich) by using LiClO 4 -DMF solutions [9,19]. To achieve this, chitin samples were mixed at 300 rpm with 100 mL of a 1.0 M LiClO 4 -DMF solution for 24 h. The LiClO 4 solution was then decanted.…”
Section: Desorption Of 'Heavy' Metals and Lanthanides From Chitinmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on previous research by the working group, it has been found that metals can be desorbed from chitin (Sigma-Aldrich) by using LiClO 4 -DMF solutions [9,19]. To achieve this, chitin samples were mixed at 300 rpm with 100 mL of a 1.0 M LiClO 4 -DMF solution for 24 h. The LiClO 4 solution was then decanted.…”
Section: Desorption Of 'Heavy' Metals and Lanthanides From Chitinmentioning
confidence: 99%
“…This implies that chitin may be a copolymer of D-glucosamine and acetyl-D-glucosamine, as illustrated in Figure 2), chitosan (ß-1→4 D-glucosamine), or 'modified' cellulose (ß-1→4 D-glucose) is a promising alternative to traditional mining processes. The utilization of biopolymers in biomining has been widely discussed in recent decades [8][9][10][11][12][13][14][15][16]. Chitin, for example, has been shown to bind a wide range of metals, mostly as Me 2+ -Ions [9,13,14,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations